Evaluating polynomial and Gaussian fitting techniques for accurate sub-index pH modeling in water quality index development - Wibowo Harry Sugiharto; Agung Budi Prasetijo; Heru Susanto (Discover Water)
Abstract This study proposes and evaluates curve-fitting models—specifically polynomial and Gaussian techniques—to accurately compute the pH sub-index as part of a Water Quality Index (WQI). This modeling is essential for enhancing the reliability of pH representation in real-time Internet of Things (IoT)-based water quality monitoring systems. By improving the pH sub-index formulation, the research aims to address one of the core components in WQI computations under dynamic environmental conditions. This work represents a critical step in the second phase of developing the IoT-based Water Quality Index (IoTWQI) framework. The resulting models are validated and compared for their suitability in sensor-based environments. The findings highlight the Gaussian Model 1 as the most accurate choice for normally distributed data (RMSE = 2.15), whereas the 6th-degree Polynomial Model remains effective in capturing complex nonlinear variations (RMSE = 4.26). These insights contribute directly to improving real-time WQI calculation performance in IoT ecosystems.